2021
DOI: 10.1097/dss.0000000000002916
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Concepts in Rheology for the Evaluation of Hyaluronic Acid–Based Soft Tissue Fillers

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 36 publications
2
77
0
Order By: Relevance
“…Biomechanical characterization of RHA fillers has demonstrated their resilient behavior, that is, improved capacity to recover their original shape and mechanical features after compression, stretching, or bending. 11 , 13 Other investigators have reported homogeneous tissue integration of RHA fillers after intradermal injection. 14…”
mentioning
confidence: 96%
“…Biomechanical characterization of RHA fillers has demonstrated their resilient behavior, that is, improved capacity to recover their original shape and mechanical features after compression, stretching, or bending. 11 , 13 Other investigators have reported homogeneous tissue integration of RHA fillers after intradermal injection. 14…”
mentioning
confidence: 96%
“…The dynamic strength of a gel describes the ability of the gel to maintain its physical integrity (G’) over a wide range of dynamic forces. The complex modulus (G*) of a gel in a dynamic environment better reflects the mechanical resistance of the gel 15 . A filler also needs to move and adapt to a dynamic face for a natural look.…”
Section: Product Selectionmentioning
confidence: 99%
“…A filler also needs to move and adapt to a dynamic face for a natural look. The stretch parameter reflects the ability of the gel to deform and adapt to stress (eg, tissue stretching when smiling) 15 . Dynamic fillers require the rheological properties of both strength and stretch to optimally treat specific areas of the face.…”
Section: Product Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, for specific medical applications, e.g., restoration of age-related volume loss in facial soft tissue, it is important to stabilize HA through a crosslinking process, which turns the otherwise liquid viscous solution into a solid-like biohydrogel, that resembles the natural structure of HA in the body and allows one to tailor mechanical, biological and rheological properties (including injectability) and resorption time [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%